The Future of Post-Covid-19 Health Services using Metaverse Technology - Joko Prasetyo; Masruroh (Journal Of Nursing Practice, 2022)
Background: The development of the metaverse technology of the next generation of the Internet, which consists of a virtual environment, Augmented Reality online which is decentralized and stable and can be widely used in the health field. Due to the growth of Metaverse technology in various fields and the importance of using it in healthcare, this study was conducted to review and identify areas of application of metaverse technology in healthcare. Purpose: The purpose of this study is to analyze the writings that examine the metaverse in health care. Methods: In this scoping review, an electronic search is done through publish or perish to get an overview by combining keywords related to the topic without a time limit. Two authors independently collected data by data extraction tables. Results: The 50 articles found through the initial search, nine studies were eligible for inclusion in the review. Most of the studies (55.55%) were published in 2021, and South Korea was the country with the most research (44.44%). The main services for using Metaverse include educational services, intervention services, and communication services. Also, medical imaging is the most practical aspect of the Metaverse used in healthcare. Conclusion: The use of Metaverse in various health fields is growing rapidly. It is now widely used in other fields, such as medical intervention and health care provision; in medical imaging, it has many applications due to fundamental changes in the nature and quality of imaging.